The state of professional orientation of schoolchildren in the modern Ukrainian school - Mohylna , Y. (New Collegium, 2021)
The article analyzes the state of the identified problem. It was found that vocational guidance in modern schools of Ukraine is conducted at a low level, is ineffective and uses a narrow range of methods. Ways to implement career guidance are mostly theoretical and do not provide sufficient knowledge for a conscious choice of profession. Lack of implementation of practical ways deprives high school students of a deep understanding of the chosen profession, the ability to conduct self-analysis and compare personal abilities and skills with the requirements for the specialty. For the most part, career guidance is reduced to the propaganda work of higher education institutions. Student visits by students and other activities organized by universities are mostly aimed at acquainting students with the peculiarities of studying in a particular university, its advantages over other educational institutions. However, such measures cannot be considered career guidance, as they do not provide sufficient information about professions, but only acquaint future entrants with the specifics of training and provide general information about the relevant professions. In addition, in Ukraine there is no relationship between the State Employment Center and the vocational guidance of schoolchildren. This leads to an imbalance between supply and demand in the labor market, which in turn negatively affects the economic situation of the country due to higher unemployment. It also has a negative impact on social development, because a person who has not been able to realize himself cannot be a socially active and life-satisfied citizen who loves his country. Due to professional uncertainty and misunderstanding by young people of the answer to the question "Who am I?" loss of flair and abilities, the development of which could bring the country advantages, victories, economic independence. Analysis of career guidance work in schools abroad shows that career guidance in schools in Ukraine is at a low level, lacks a number of important components and does not have a positive impact on the social and economic life of the country.